Artist-Directed Inverse-Kinematics Using Radial Basis Function Interpolation - Rose III, Charles F.; Sloan, Peter-Pike J.; Cohen, Michael F. (Computer graphics forum, 2001)
One of the most common tasks in computer animation is inverse‐kinematics, or determining a joint configuration required to place a particular part of an articulated character at a particular location in global space. Inverse‐kinematics is required at design‐time to assist artists using commercial 3D animation packages, for motion capture analysis, and for run‐time applications such as games. We present an efficient inverse‐kinematics methodology based on the interpolation of example motions and positions. The technique is demonstrated on a number of inverse‐kinematics positioning tasks for a human figure. In addition to simple positioning tasks, the method provides complete motion sequences that satisfy an inverse‐kinematic goal. The interpolation at the heart of the algorithm allows an artist's influence to play a major role in ensuring that the system always generates plausible results. Due to the lightweight nature of the algorithm, we can position a character at extremely high frame rates, making the technique useful for time‐critical run‐time applications such as games.